Diet supplemented with fermented onion improves growth performance, health condition, meat quality, and modifies rumen metabolite profiles in Liangshan black sheep - Jiang, Shengwang; Yang, Chaoyun; Ji, Chen; Li, Chao; Lv, Gang; Gao, Hongwei; Zhang, Wei; Zhang, Yi; Huang, Zengwen (Frontiers in Veterinary Science, 2025)
This study aims to investigate the effect of fermented onion on Liangshan black sheep’s growth performance, health, meat quality, and rumen metabolite profiles. A total of 80 four-month-old female Liangshan black sheep were randomly divided into four groups of five replicate pens (four sheep per pen). Sheep were fed a basal diet supplemented with 0 (control), 10, 20% or 30% fermented onion. Compared to that of the control group, dietary supplementation with 20% fermented onion improved final body weight, ADG and ADFI; enhanced GPT and GOT activities and increased IgA, IgG, IgM, C3, and C4 levels; increased the levels of IL-4, IL-10, TGF-β and decreased the levels of IL-1β, IL-6, TNF-α, IFN-γ; decreased MDA level and increased SOD, GST, CAT and GSH-Px activities; decrease the pH, L* value, b* value and shear force; increase the a* value and the content s of protein and fat; increase the expression levels of FN1, TGFβ1, Myf5, FAS, PPARγ and FABP4; decrease the expression levels of CPT1A and LPL. Metabolomic analysis revealed that 20% fermented onion supplementation significantly modified the metabolite profiles in the rumen liquid, with 44 downregulated metabolites and four upregulated metabolites mainly enriched in purine metabolism, microbial metabolism, cutin, and suberine biosynthesis pathways. Data from our study suggest that supplementation of fermented onion to the basal diet at 20% (w/w) can be used safely to increase meat yield and to improve meat quality in the sheep industry.